1995
DOI: 10.1515/znb-1995-0703
|View full text |Cite
|
Sign up to set email alerts
|

Oligophosphan-Liganden, XXXIX. (1S,2S)-trans-Cyclopentan-1,2-diyl-bis(phosphan), C5H8(PH2)2, durch Reduktion eines diastereomerenreinen Cyclopentandiyl-bis(dioxaphospholans) / Oligophosphine Ligands, XXXIX. (1 S,2S)-trans-Cyclopentane-1,2-diyl-bis(phosphine), C5H8(PH2)2, by Reduction of a Diastereomerically Pure Cyclopentanediyl-bis(dioxaphospholane)

Abstract: The title compound (S,S)-2, has been obtained by reduction with Li[AlH4] of the cyclopentane- 1,2-diyl-bis(1′,3′,2′-dioxaphospholane) (1S ,2S)-trans-C5H8[P(OCH (CO2Pr-i)- (R) - )2]2, (S,S)-1, which itself was isolated in diastereomerically pure form (X-ray structure analysis) from the reaction between rac, trans-C5H8(PCl2)2 and (2R,3R)-(+)-diisopropyl tartrate. Cleavage of (S,.S)-1 withPCl3 yielded an unseparable mixture of (1S,2S)-trans-C5H8(PCl2)2 and (4R.5R) -ClP [OCH(CO2Pr-i)-]2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In synthetic organophosphorus chemistry, aromatic and some aliphatic bis-phosphonites and bis-phosphonate esters such as A [7], B [8], C [9], D [10,11] and E [12] (Fig. 1) are valuable starting materials for the preparation of primary bis-phosphines [11,13] which have been successfully used for the synthesis of chiral bis-phosphines, e. g. 1,2-bis(phospholano)benzenes such as the DuPHOS-(A') and PennPHOS ligands (A'') [14], 1,1'-bis(2,5-dialkylphospholano)ferrocenes D' [10], duthixantphospholane-type (C') [9] and other chiral and non-chiral ligands [15] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In synthetic organophosphorus chemistry, aromatic and some aliphatic bis-phosphonites and bis-phosphonate esters such as A [7], B [8], C [9], D [10,11] and E [12] (Fig. 1) are valuable starting materials for the preparation of primary bis-phosphines [11,13] which have been successfully used for the synthesis of chiral bis-phosphines, e. g. 1,2-bis(phospholano)benzenes such as the DuPHOS-(A') and PennPHOS ligands (A'') [14], 1,1'-bis(2,5-dialkylphospholano)ferrocenes D' [10], duthixantphospholane-type (C') [9] and other chiral and non-chiral ligands [15] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The dioxaphospholane (S,S)-1 11 was hydrolyzed in hydrochloric acid leading to the free phosphinic acid (S,S)-2, which was isolated and characterized. In the second step (S,S)-2 was chlorinated by stirring in PCl 3 giving the desired bisphosphonous acid dichloride (S,S)-3 in 21% total yield.…”
Section: Methodsmentioning
confidence: 99%
“…10 The key step, the crystallization of a single diastereomer formed with (+)-diisopropyl tartrate (DIPT), had been published earlier. 11 We used it to develop an alternative route to the chiral dichlorophosphane (S,S)-3 compared to that described in Ref. 10 (Scheme 1).…”
Section: Synthesis Of the Chiral Precursor (1s2s)-12-bis(dichlorophmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important breakthrough in the resolution of the enantiomers of the bis(phosphonous dichloride) L Cl , we found that the cyclopentane‐1,2‐diyl[bis(1′,3′,2′‐dioxaphospholane] L tart resulting from the reaction of rac ‐ L Cl with (2 R ,3 R )‐(+)‐diisopropyl tartrate (Scheme ) could be crystallized from the isomeric mixture as a single (1 S ,2 S ,4′ R ,5′ R ) diastereomer, ( S , S )‐ L tart ‐( R , R ) 25. As expected, the (1 R ,2 R ,4′ S ,5′ S ) enantiomer, ( R , R )‐ L tart ‐( S , S ) , was isolated, isomerically pure, from a similar reaction employing (2 S ,3 S )‐(−)‐diisopropyl tartrate as the diol component 26a.…”
Section: The Ligandsmentioning
confidence: 99%